2001
DOI: 10.1002/1097-0142(20010715)92:2<263::aid-cncr1318>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Radioisotope-guided surgery in patients with pheochromocytoma and recurrent medullary thyroid carcinoma

Abstract: BACKGROUND The objective of this study was to appraise the detection of metastases of medullary thyroid carcinoma (MTC) and pheochromocytoma using radioguided surgery (RGS) and to compare the results with external imaging modalities, surgical palpation, and histopathologic findings. METHODS Twenty‐five patients with recurrent MTC underwent preoperative scintigraphic imaging with 500 megabecquerels (MBq) of technetium 99m(V)‐dimercaptosuccinic acid [99mTc(V)‐DMSA] and 222 MBq of indium 111 (111In)‐pentetreotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, to identify the metastatic lymph nodes during reoperation, many methods were reported to be used for localization, such as hook-needle, intraoperative ultrasound, radio-guided surgery, and dyes. [2022] With respect to the dyes, the initial lymph tracer was methylene blue, which may cause local infection and it diffused so easily that the time of surgery was limited. [23] Afterward, charcoal tattooing was extensively used as lymph tracer for tumor operation, but it lacks the directivity for lymphatic system because of its varied particle size.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to identify the metastatic lymph nodes during reoperation, many methods were reported to be used for localization, such as hook-needle, intraoperative ultrasound, radio-guided surgery, and dyes. [2022] With respect to the dyes, the initial lymph tracer was methylene blue, which may cause local infection and it diffused so easily that the time of surgery was limited. [23] Afterward, charcoal tattooing was extensively used as lymph tracer for tumor operation, but it lacks the directivity for lymphatic system because of its varied particle size.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of 131 I-MIBG (meta-iodobenzyl-guanidine) for the detection of MTC is 29-30% [25], and the sensitivity of SRS ranges from 25 to 50% [5,26].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lesions less than 1 cm are not effectively detected by SRS. 104 The sensitivity of SRS also correlates with hCT levels. 105 A study using [ 68 Ga] DOTATATE reported a per-patient sensitivity of 72%, compared to 78% for FDG.…”
Section: Medullary Thyroid Carcinomamentioning
confidence: 99%